2007
DOI: 10.1016/j.jasms.2006.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Mass-tag technology responding to intracellular signals as a novel assay system for the diagnosis of tumor

Abstract: A novel mass spectrometry-based assay system for determining protein kinase activity employing mass-tagged substrate peptide probes was used for the diagnosis of tumors. Two peptide probes (H-type and D-type) were synthesized containing the same substrate peptide sequence for protein kinase C (PKC). The molecular weights of the two probes differ because of the incorporation of deuterium into the acetyl groups of the D-type probe. The lysates of the normal and tumor tissue were prepared and reacted with the H-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…In a previous study, we found that the substrate (FKKQGSFAKKK) showed a higher phosphorylation ratio on PKC␣ [22]. Here, the same substrate was used in the phosphorylation reaction for PKC␣.…”
Section: Phosphorylation Of Two Substrates By Target Enzymementioning
confidence: 93%
See 1 more Smart Citation
“…In a previous study, we found that the substrate (FKKQGSFAKKK) showed a higher phosphorylation ratio on PKC␣ [22]. Here, the same substrate was used in the phosphorylation reaction for PKC␣.…”
Section: Phosphorylation Of Two Substrates By Target Enzymementioning
confidence: 93%
“…Means of the phosphorylation ratio obtained from three spots selected manually on the crystals were used as results for assay purposes. The phosphorylation ratio is defined as the ratio of ion intensities for the phosphorylated to unphosphorylated material, and this was calculated as described previously [22] .…”
Section: Maldi-tof Mass Spectrometrymentioning
confidence: 99%
“…Fluorescence polarization, bead techniques using fluorimetry and colorimetric assays offer a way to reach this goal. Mass spectrometry is also a promising approach Kang et al, 2007;Shigaki et al, 2006). Peptide arrays are another promising technology for detail evaluation of cellular conditions.…”
Section: Conclusion and Future Prospectivementioning
confidence: 99%
“…In the present study, CHCA was used as a matrix for analysis. Phosphorylation of the substrate by PKCα was identified by an increase in the m/z value of +80 Da ( Figure 1) [18,19].…”
Section: Phosphorylation Of Peptide Substrate By Recombinant Pkcα αmentioning
confidence: 99%